How the Influence of Unethical Leaders on Followers Is Affected by Their Implicit Followership Theories. (November 2017) - Knoll, Michael; Schyns, Birgit; Petersen, Lars-Eric
Our research examines the role of followers in unethical leadership. Drawing on a social–cognitive approach to leadership and recent research in the field of behavioral ethics, we focus on how leader behavior and follower information processing interact to produce unethical outcomes. In two experimental studies simulating a personnel selection context, we examine to what extent individual implicit assumptions regarding the follower role (i.e., implicit followership theories, IFTs) relate to employees' tendency to comply with leader unethical suggestions. In Study 1, controlling for possible alternative explanations such as personal need for structure, romance of leadership, and moral disengagement, we found that the IFT Good Citizen increased and the IFT Insubordination decreased followers' tendencies to contribute to unethical leadership. In Study 2, we varied the leader's unethical suggestions to further investigate the conditions under which these effects occur and included authoritarianism as an additional control variable. Overall, our findings suggest that IFTs make a unique contribution to our understanding of the role of followers in unethical leadership, and that this contribution depends on the way leaders frame their unethical request. Interaction effects suggest that follower characteristics need to be considered as they are embedded in specific situational settings rather than as isolated traits.